2008
DOI: 10.1111/j.1835-2561.2008.0028.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of International Financial Reporting Standards: Impact on the Value Relevance of Intangible Assets

Abstract: We examine whether the value relevance of reported intangibles differs between financial reporting regimes pre‐ and post‐adoption of Australian Equivalents to International Financial Reporting Standards (AIFRS) and Australian Accounting Standards (AGAAP) respectively. Using AIFRS and AGAAP measures of goodwill and identifiable intangible assets for the same financial year and testing their association with share prices, we find evidence that AIFRS generally convey incremental useful information for investors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
97
2
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 20 publications
10
97
2
14
Order By: Relevance
“…This is in harmony with the results of Bartov et al (2005), Hung and Subramanyam (2007), Barth et al (2008), Chalmers et al (2008), Curto (2009), Chalmers et al (2009), Kadri et al (2009) and Lima (2011), who also found an improvement in the information content of the financial statements after the process of convergence to international accounting standards.…”
Section: Table 4 Results Of the Regression With Seps And Wcpssupporting
confidence: 66%
See 1 more Smart Citation
“…This is in harmony with the results of Bartov et al (2005), Hung and Subramanyam (2007), Barth et al (2008), Chalmers et al (2008), Curto (2009), Chalmers et al (2009), Kadri et al (2009) and Lima (2011), who also found an improvement in the information content of the financial statements after the process of convergence to international accounting standards.…”
Section: Table 4 Results Of the Regression With Seps And Wcpssupporting
confidence: 66%
“…In this area, the work of Bartov, Goldberg, and Kim (2005) Chalmers, Clinch, and Godfrey (2008), Curto (2009), Chalmers, Clinch, andGodfrey (2009), Kadri, Aziz, and Ibrahim (2009) and Lima (2011) showed gains in the relevance of accounting information when there was a migration from a local standard to the international standard. In the contrary sense, the work of Niskaen, Kinnunen, and Kasanen (2000), Van der Meulen, Gaeremynck, and Willekens (2007) and Morais and Curto (2008) showed that changes resulting from the process of accounting harmonization with IFRS did not give rise to any gains in relevance, or that any such changes were not significant.…”
Section: Value Relevance: the Study Of The Relevance Of Accounting Inmentioning
confidence: 99%
“…They argue that the change in the accounting system potentially reduce earnings manipulation practices due to more restrictive requirements, thus leading to the recognised amounts of these expenditures being regarded by the investors as having future economic benefits. Meanwhile, [13] examine the effect of IFRS adoption on the value relevance of intangible assets in Australia. Based on a sample of 599 ASX firms listed in 2006, they compare the Australian GAAP and IFRS balances for goodwill and identifiable intangible assets reported in the annual reports.…”
Section: B Accounting For Intangible Assets Value Relevance and Firmentioning
confidence: 99%
“…AASB 138 "Intangibles" is an Australian equivalent of International Financial Reporting Standard (AIFRS). Adoption of AIFRS significantly changed the measurement and recognition practices for goodwill in Australia (Chalmers, Clinch, & Godfrey, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…AASB 138 "Intangibles" is an Australian equivalent of International Financial Reporting Standard (AIFRS). Adoption of AIFRS significantly changed the measurement and recognition practices for goodwill in Australia (Chalmers, Clinch, & Godfrey, 2008).Market capitalization of listed firms as measured by quoted share prices is generally higher than the book value of the net assets of listed firms. For many firms, the difference between these two measures is significant.…”
mentioning
confidence: 99%